RETRACTED ARTICLE: Synthesis of silver nanoparticles using Plantago lanceolata extract and assessing their antibacterial and antioxidant activities - Muhammad Zahir Shah; Zheng-Hui Guan; Ala Ud Din; Amjad Ali; Ata Ur Rehman; Kashif Jan; Shah Faisal; Shah Saud; Muhammad Adnan; Fazli Wahid; Saud Alamri; Manzer H. Siddiqui; et al. (Scientific Reports)
Abstract Silver nanoparticles (Ag. NPs) have shown a biological activity range, synthesized under different environment-friendly approaches. Ag. NPs were synthesized using aqueous crude extract (ACE) isolated from Plantago lanceolata. The ACE and Ag. NPs were characterized and assessed their biological and antioxidant activities. The existence of nanoparticles (NPs) was confirmed by color shift, atomic force microscopy (AFM), and UV–Vis’s spectroscopy. The FT-IR analysis indicated the association of biomolecules (phenolic acid and flavonoids) to reduce silver (Ag+) ions. The SEM study demonstrated a sphere-shaped and mean size in the range of 30 ± 4 nm. The EDX spectrum revealed that the Ag. NPs were composed of 54.87% Ag with 20 nm size as identified by SEM and TEM. AFM has ended up being exceptionally useful in deciding morphological elements and the distance across of Ag. NPs in the scope of 23–30 nm. The TEM image showed aggregations of NPs and physical interaction. Ag. NPs formation also confirmed by XPS, DRS and BET studies. Ag. NPs showed efficient activity as compared to ACE, and finally, the bacterial growth was impaired by biogenic NPs. The lethal dose (LD50) of Ag. NPs against Agrobacterium tumefaciens, Proteus vulgaris, Staphylococcus aureus, and Escherichia coli were 45.66%, 139.71%, 332.87%, and 45.54%, with IC50 (08.02 ± 0.68), (55.78 ± 1.01), (12.34 ± 1.35) and (11.68 ± 1.42) respectively, suppressing the growth as compared to ACE. The antioxidant capacity, i.e., 2,2-diphenyl-1-picrylhydrazyl (DPPH) of Ag. NPs were assayed. ACE and Ag. NPs achieved a peak antioxidant capacity of 62.43 ± 2.4 and 16.85 ± 0.4 μg mL−1, compared to standard (69.60 ± 1.1 at 100 μg mL−1) with IC50 (369.5 ± 13.42 and 159.5 ± 10.52 respectively). Finally, the Ag. NPs synthesized by P. lanceolata extract have an excellent source of bioactive natural products (NP). Outstanding antioxidant, antibacterial activities have been shown by NPs and can be used in various biological techniques in future research.